Stress, appraisal, and coping - Lazarus, Richard S. (Springer Publishing Company, 1984)
Here is a monumental work that continues in the tradition pioneered by co-author Richard Lazarus in his classic book Psychological Stress and the Coping Process. Dr. Lazarus and his collaborator, Dr. Susan Folkman, present here a detailed theory of psychological stress, building on the concepts of cognitive appraisal and coping which have become major themes of theory and investigation.As an integrative theoretical analysis, this volume pulls together two decades of research and thought on issues in behavioral medicine, emotion, stress management, treatment, and life span development. A selective review of the most pertinent literature is included in each chapter. The total reference listing for the book extends to 60 pages.